MEMPROGRAMKAN PENGENALAN BANK SYARIAH DAN LEMBAGA KEUANGAN MIKRO SYARIAH DI DESA CIBITUNG TENGAH, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Rully Trihantana; Ria Kusumaningrum; Rafiduddin (SAHID DEVELOPMENT JOURNAL, 2023)
Community service activities aim to increase a comprehensive and integrative understanding of the people of Central Cibitung Village, Tenjolaya District, Bogor Regency, regarding Islamic banking and Islamic microfinance institutions. Activities to introduce sharia banking and sharia microfinance institutions to the public need to be provided to open up insights about sharia banking. The result of this activity is that the people of Central Cibitung Village have knowledge of Islamic banking and Islamic microfinance institutions, and have the desire to save or even invest in Islamic banks around the Bogor Regency area.